Safeguarding the Intangible Cultural Heritage Through a Tri-sector Model: The Jewellery Quarter in the Old City of Istanbul - Oten, Ayse Nur; Evren, Yigit (KARE PUBL, 2013)
This paper discusses the possibilities of reviving the traditional craftsmanship in its original, historic location through a bottom-up approach. The jewellery production in the Old City of Istanbul is clustered in the Grand Bazaar (Kapalicarsi) and its vicinity where the crafts' characteristics has been embedded into the built environment. The traditions of production and urban life are merged in this part of the Old City. Therefore, the authors designate this specific area as the jewellery quarter and propose a tri-sector regeneration approach through which the artisans in the area can safeguard their craft and place relying on the local social capital. In this context, this paper proposes an Artisan-led Regeneration Model which allows craftsmen to initiate regeneration projects at various scales while relying on institutional support and guidance of local jewellers. The model assumes that collaboration and solidarity can be orchestrated by a non-governmental organization such as the Jewellery Quarter Foundation. Furthermore, the model assumes that a bottom-up regeneration policy should be compresensive and give priority to social and economic development in the area. Thus, a multipurpose center is proposed to serve as the headquarters of the regeneration where artistic, cultural, social, and educational activities as well as spatial improvemens can be administered. The third proposition of the model is to introduce tenant artisans as one of the rightful stakeholders into the legal system concerning urban operations. Including the tenant artisans into the institutional structure would reinforce the grassroots character of the regeneration process and diminish the risk of gentrification.
Keywords: Regeneration; jewellery making; participation; intangible cultural heritage; tri-sector partnership; craftsmanship; SPACE; Public Administration